The ecology of the saline lakes in the semiarid Pampa central (Argentina): limnological characterization and zooplankton of Utracán - Echaniz, Santiago Andrés (2015)
In the semi-arid central Argentina exist temporary saline lakes that have recently begun to be studied. If salinity does not exceed 30 g.L-1 can be studied using the "alternative states of shallow lakes model". The aim of this study was to determine the ecology of a limnologically unknown lake during a mesosaline period and to verify that due to the salinity, zooplankton richness, density and biomass were similar to other lakes in the region and, due to the fishes’ lacking, the zooplankton is consisted of larger species, which contributes to the clear state. The depth and salinity remained stable (2 ± 0.15 m and 32.9 ± 2.7 g.L-1 ). Although high concentrations of nutrients, transparency exceeded 1.1 m and chlorophyll-a concentration was around 1 mg.m-3 . The ratio Zm / Zphot was 0.62 (clear state). Two cladocerans, two copepods and two rotifers were registered and no correlation between richness and environmental parameters was found. The greatest density and biomass was provided by copepods, especially Boeckella poopoensis Marsh, 1906. The zooplankton biomass was lower than other Pampean lakes, probably by the limited availability of food derived of the clear state. A particularity of the lake was the reduced influence of environmental factors on zooplankton, probably due to varied in narrow ranges and the species remained within its tolerances ranges.